Damage tolerance of 2-dimentional UHMWPE/CF hybrid woven laminates subjected to low-velocity impact - Yuan Hu; Yaoyao Shi; Dongsheng Liu; Jian Guo; Junfeng Zhang; Zhen Chen (Materials & Design, 2020)
Carbon fiber reinforced polymer composite laminates (CFRPs) with weak impact damage tolerance were toughened with Ultra-high Molecular Weight Polyethylene (UHMWPE) fiber in the form of two-dimensional hybrid weaving in this paper. The effects of hybrid woven on impact behaviour and residual flexural stiffness of CFRPs, compared with plain carbon-fiber woven laminates, were investigated by drop weight impact and four-point bending experimental tests, together with finite element analysis (FEA). Indentation measurement and X-ray tomography, together with Scanning Electron Microscope (SEM) were employed for a comprehensive inspection of external and internal damage of specimens subjected to impact previously. A significant increment of 71.43% in penetration energy revealed the lower sensitivity of hybrid laminates to impact events in comparison with the pure carbon fiber reinforced ones, while post-impact flexural tests demonstrated that two-dimensional hybrid weaving was capable of bringing about a promotion of 10.1% in damage tolerance. The suppression mechanism of damage propagation in impact test, which lead to an enhancement in damage tolerance and structural integrity, was explained.